Vivências de professores de matemática com o uso de tecnologias digitais de informação e comunicação (TDIC) em tempos de pandemia. - Jesus, Sônia Máximo de (Universidade Federal do Tocantins, 2023)
The transformations that occurred with the beginning of the Covid-19 pandemic caused several changes in education and consequently in the practices of teachers, as well as in society, particularly in the cultural and social economic contexts. In education, there was a need for social distancing and with this activities in face-to-face teaching were suspended, making it necessary to adopt remote teaching as a teaching and learning process combined with the use of Digital Information and Communication Technologies (TDIC). Thus, the present work aims to analyze the difficulties encountered by teachers when teaching mathematics in the remote model, using the TDIC, during the Covid-19 pandemic, at Escola Estadual Girassol de Tempo Integral Combinado, in the municipality of Combinado (TO). The use of TDIC challenged the entire school community to adapt to this new senários, where the center of this process is the student and the teacher is the main mediator facing challenges in a co-responsible way in the school environment. Therefore, we carried out a research with a qualitative approach, using a semi-structured questionnaire for data analysis, prepared and sent through e-mail and dialogues through Whastapp message, to be answered by teachers from the public school system in the State of Ceará. Tocantins, seeking to analyze the difficulties encountered by these teachers when using TDIC during the pandemic. The results on the transmission process of these teachers to remote teaching, highlighting the lack of familiarity and training with the TDICs, indicating the limitations of initial and continued training regarding their use.